An unusual presentation of a calcified thyroid gland. (10th December 2012) - Lyons, Rebecca; Waters, Peadar S; Sugrue, Conor; Kerin, Michael J
Abstract : A multinodular goitre with cystic degeneration with haemorrhage and subsequent calcification is a common occurrence in long-standing multinodular goitres. But extensive enlargement and calcification causing obstructive symptoms including dysphagia and tracheal shift has not been commonly reported in the literature. Our patient, an 82-year-old man presented with long-standing dysphagia and tracheal shift. His case proved challenging with the retrosternal location of the calcified gland, needing a collar neck incision and a manubriotomy to assess the thyroid. There was a large calcified shell to the gland that made mobilising and removing the gland very difficult. Histology revealed a large multinodular goitre with a large calcified cyst representing previous cyst haemorrhage which underwent calcification. Symptoms resolved postsurgical intervention.